Computer Graphics - Computer Art. - Franke, Herbert W. (London : Phaidon Press Limited, 1971)
Adrian, Marc ; Alsleben, Kurd ; Beckmann, Otto ; Citron, Jack P. ; Group, Computer Technique ; Cordeiro, Waldemar ; Csuri, Charles ; Fetter, William A. ; Henne, Peter ; Knowlton, Kenneth C. ; Kreis, Peter K. ; Laposky, Ben F. ; Lecci, Auro ; Mezei, Leslie ; Mohr, Manfred ; Mott-Smith, John C. ; Nake, Frieder ; Nash, Katherine ; Nees, Georg ; Noll, A. Michael ; Palyka, Duane M. ; Peterson, H. Philip ; Rase, Ludwig ; Schroeder, Manfred R. ; Schwartz, Lillian F. ; Struycken, Peter ; Sumner, Lloyd ; Sutcliffe, Alan ; Thomas, Klaus ; Whitney, John
Biografie, Bibliografie
Engels
boek